Human Platelet Lysate Improves Bone Forming Potential of Human Progenitor Cells Expanded in Microcarrier‐Based Dynamic Culture. (30th April 2019) - Gupta, Priyanka; Hall, Gabriella Nilsson; Geris, Liesbet; Luyten, Frank P.; Papantoniou, Ioannis
Abstract: Xenogeneic‐free media are required for translating advanced therapeutic medicinal products to the clinics. In addition, process efficiency is crucial for ensuring cost efficiency, especially when considering large‐scale production of mesenchymal stem cells (MSCs). Human platelet lysate (HPL) has been increasingly adopted as an alternative for fetal bovine serum (FBS) for MSCs. However, its therapeutic and regenerative potential in vivo is largely unexplored. Herein, we compare the effects of FBS and HPL supplementation for a scalable, microcarrier‐based dynamic expansion of human periosteum‐derived cells (hPDCs) while assessing their bone forming capacity by subcutaneous implantation in small animal model. We observed that HPL resulted in faster cell proliferation with a total fold increase of 5.2 ± 0.61 in comparison to 2.7 ± 02.22‐fold in FBS. Cell viability and trilineage differentiation capability were maintained by HPL, although a suppression of adipogenic differentiation potential was observed. Differences in mRNA expression profiles were also observed between the two on several markers. When implanted, we observed a significant difference between the bone forming capacity of cells expanded in FBS and HPL, with HPL supplementation resulting in almost three times more mineralized tissue within calcium phosphate scaffolds. FBS‐expanded cells resulted in a fibrous tissue structure, whereas HPL resulted in mineralized tissue formation, which can be classified as newly formed bone, verified by μCT and histological analysis. We also observed the presence of blood vessels in our explants. In conclusion, we suggest that replacing FBS with HPL in bioreactor‐based expansion of hPDCs is an optimal solution that increases expansion efficiency along with promoting bone forming capacity of these cells.Stem Cells Translational Medicine 2019;8:810&821 Abstract : In this study, human platelet lysate (hPL) supplementation was seen to improve expansion efficiency but also bone forming potential of Human periosteum derived progenitors as to those expanded in fetal bovine serum containing medium. This improvement in potency was associated to the activation of WNT and BMP signaling in the hPL expanded cells. This provides a xenogeneic free medium that shows a dual improvement in terms of process and product efficiency in a scalable microcarrier‐based dynamic culture.